Evaluation of MALDI-TOF VITEK®MS and VITEK® 2 system for the identification of Staphylococcus saprophyticus - Martins, Katheryne B. [UNESP]; Ferreira, Adriano M. [UNESP]; Mondelli, Alessandro L. [UNESP]; Rocchetti, Taisa T. [UNESP]; Lr De S Da Cunha, Maria De [UNESP] (My University, 2018)
Aim: To compare two identification methods for coagulase-negative staphylococci (CoNS) isolated from patients with urinary tract infections, VITEK® 2 and MALDI-TOF VITEK®MS, with genotypic identification by internal transcribed spacer PCR (ITS-PCR). Results: A total of 217 CoNS isolates were studied. Agreement of the VITEK® 2 system with ITS-PCR was 84.8%, with 98% sensitivity and 100% specificity. Thirty-one of the 33 strains incorrectly identified by VITEK® 2 belonged to the species Staphylococcus saprophyticus. MALDI-TOF VITEK®MS showed an excellent correlation with ITS-PCR since it correctly identified all CoNS isolates. Conclusion: MALDI-TOF VITEK®MS is more accurate than the automated VITEK® 2 system in identifying CoNS isolated from urinary tract infections to species level, particularly urinary isolates of S. saprophyticus.
Keywords: CoNS; identification methods; ITS-PCR; MALDI-TOF VITEK®MS; urinary tract infection; VITEK® 2